State social policy in developing family entrepreneurship in agriculture - Khujakulova Nigora Rustamovna; Sharofova Saida Alimurat kizi (THE INNOVATION ECONOMY, 2026)
This article analyzes the state’s social policy in the development of family entrepreneurship in agriculture, the ongoing comprehensive reforms, the work being carried out to comprehensively support the development of family entrepreneurship and systematically organize work in this area. It also examines the development and sig nificance of family entrepreneurship in the agricultural sector of Uzbekistan, the problems that arise in this area and ways to solve them